(untitled) (Prosiding Keislaman dan Sains, 2025)
The purpose of this study was to determine one of the appropriate learning methods in the development of Religious and Moral Values ​​of children aged 5-6 years, namely the Ladder of Sholeh Children Learning Method. This study uses a quantitative method with a pre-experimental design research type. Using one class in the form of a pre-test and post-test design. Data collection techniques used are observation and documentation. The results of this study are based on the normality test and hypothesis data (t-test), namely the calculated t value> t table, namely 11.859> 1.833, which means that the Ha test is accepted and Ho is rejected. So it can be concluded that there is an influence of the TAS (Tangga Anak Sholeh) learning method in developing religious and moral values ​​of children aged 5-6 years. Based on the analysis of the research results and the discussion above, it can be concluded that the application of the TAS (Tangga Anak Sholeh) learning method has an effect on the development of religious and moral values ​​of children aged 5-6 years at PAUD Kasih Bunda, Bandar Sei Kijang District, Pelalawan Regency. The results of this study are expected to be used as information in developing religious and moral values ​​at an early age, especially at the age of 5-6 years, by using various media, especially the TAS (Tangga Anak Sholeh) learning method.